2011
DOI: 10.1111/j.1365-3059.2011.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant height on type I and type II resistance to fusarium head blight in wheat

Abstract: By carefully separating type I and type II resistances, the possible effects of plant height on fusarium head blight (FHB) resistance in wheat were assessed using near-isogenic lines (NILs) for several different reduced-height (Rht) genes. Tall isolines all gave better type I resistance than their respective dwarf counterparts when assessed at their natural heights. These differences largely disappeared when the dwarf isolines were physically raised so that their spikes were positioned at the same height as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 41 publications
7
40
0
Order By: Relevance
“…Short plants have higher disease levels due to the microclimate around the spike where high moisture and humidity and close proximity to the inoculum are favorable for increased disease [50]. Yan et al [51] demonstrated this result by studying near-isogenic lines for Rht genes. His group observed that tall plants were more resistant to infection (type I) than the semi-dwarf phenotypes, however when both phenotypes were at the same height that difference disappeared [51].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Short plants have higher disease levels due to the microclimate around the spike where high moisture and humidity and close proximity to the inoculum are favorable for increased disease [50]. Yan et al [51] demonstrated this result by studying near-isogenic lines for Rht genes. His group observed that tall plants were more resistant to infection (type I) than the semi-dwarf phenotypes, however when both phenotypes were at the same height that difference disappeared [51].…”
Section: Discussionmentioning
confidence: 63%
“…Yan et al [51] demonstrated this result by studying near-isogenic lines for Rht genes. His group observed that tall plants were more resistant to infection (type I) than the semi-dwarf phenotypes, however when both phenotypes were at the same height that difference disappeared [51].…”
Section: Discussionmentioning
confidence: 79%
“…DELLA proteins have been shown to be associated with abiotic and biotic stress tolerance (Achard and Genschik 2009) and, in the case of FHB, a DELLA protein mutation may have physiological effects linked to changes in cell death response (Saville et al 2012). Alternatively to these genetic effects, differences in microclimatic conditions around the heads of tall and dwarf genotypes have been considered to play a significant role particularly under field conditions, with short plants being exposed to higher infection pressure than tall plants (Yan et al 2011). The Rht - B1b allele is also known to have pleiotropic effects on different morphological and structural traits including reduced peduncle length and increased cell density, which may also affect response to FHB.…”
Section: Discussionmentioning
confidence: 99%
“…Plant height is one of the foremost morphological traits affecting FHB response and the widely deployed Norin 10 semi-dwarfing Rht alleles, namely Rht - B1b and Rht - D1b , have been found associated with increased FHB severity under field conditions in common wheat (Hilton et al 1999; Miedaner and Voss 2008; Voss et al 2008) and in durum wheat (Buerstmayr et al 2012). Their effect on FHB development may be imputed to plant height per se and differences in canopy structure (Yan et al 2011) as well as to pleiotropic physiological effects of the Rht genes and/or the presence of tightly linked genes (Srinivasachary et al 2009; Saville et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Clearly, crown and spikes have different structures and they are also exposed to different microenvironments (temperature and humidity) due to their different distances from the soil surface. Previous studies showed that these factors affect the development of both FHB [25] and FCR [26]. …”
Section: Discussionmentioning
confidence: 99%